The roles of aspirations, coefficients and utility functions in multiple objective decision making. (September 2019) - Zhao, Wen-Xuan; Ho, Hui-Ping; Chang, Ching-Ter
Highlights: The proposed model allows decision maker to set multi-group pricing discrimination strategy. The qualitative and quantitative issues are considered. The multiple coefficients, aspirations and utility functions are addressed. Abstract: Decisions using multiple aspiration levels, coefficients, and utility functions to maximize profit/minimize cost are commonly seen in many companies. Understanding the roles of these factors may improve decision making effectiveness. However, the roles of these techniques are rarely discussed in conjunction with solving real problems. This paper addresses the roles of aspirations levels, coefficients attached to the objective/constraints and utility functions for representing the decision makers' preference. Accordingly, a decision maker can easily use these techniques to solve their management/decision problems. This study creates several practical models to improve their utilization in the decision and management fields. In addition, new utility functions are also proposed as a qualitative tool to enrich the usefulness of the proposed models and increase the usage of MODM methods in solving business decision problems. In short, both qualitative and quantitative problems are considered at the same time in the proposed model to deal with more real-world situations. Therefore, the usefulness of the proposed methods in the MODM field is improved.